Rates of proximal deep vein thrombosis as assessed by compression ultrasonography in patients receiving prolonged thromboprophylaxis with low molecular weight heparin after major orthopedic surgery - Schellong, Sebastian; Hesselschwerdt, Hans-Jürgen; Paar, W Dieter; von Hanstein, Karl-Ludwig (Thrombosis and haemostasis, 2005)
Patients undergoing major orthopedic surgery are at an increased risk of thromboembolism even after the acute postoperative phase. Therefore, prolonged thromboprophylaxis is currently recommended and widely used. The length of hospital stay after major orthopedic surgery is steadily decreasing and most patients are transferred to specialized rehabilitation centers in the early postoperative phase. Consequently, thromboprophylaxis is usually given during the rehabilitation period. Previously there have been no systematic studies of how many patients with asymptomatic thrombosis are transferred to a rehabilitation center or how many patients develop deep vein thrombosis (DVT) during rehabilitation. In the present study, 238 patients who had undergone major orthopedic surgery were examined by compression ultrasonography on day 1 or 2 and on day 20 of their rehabilitation phase in order to detect asymptomatic proximal DVT. Sonograms were read centrally with blinding to the clinical course of the patients. All patients received standard thromboprophylaxis during the acute postoperative phase. Prolonged thromboprophylaxis with enoxaparin was given during the rehabilitation phase. The mean duration of thromboprophylaxis was 36.8 days. At admission to the rehabilitation center, proximal DVT was identified in 16 patients (6.7%). New proximal DVT at discharge from the rehabilitation center was identified in 3.2% of patients following prolonged thromboprophylaxis with enoxaparin. In conclusion, a considerable percentage of patients with asymptomatic proximal DVT are transferred to rehabilitation centers following major orthopedic surgery. Using prolonged thromboprophylaxis, new proximal DVTs will still develop during rehabilitation, but at a low rate.